Analisis Rasio untuk Menilai Laporan Keuangan pada KPRI SEJAHTERA Dinas Pertanian Blitar - Vigna Triwulan Puspitasari (Universitas Islam Kadiri, 2018)
This study aims to analyze: 1. Financial Performance of KPRI SEJAHTERA Cooperative Based on Liquidity Ratio in review of (Current Ratio, Quick Ratio, Cash Ratio); 2. Financial Performance of KPRI SEJAHTERA Cooperative Based on Solvency Ratio in review of (Total Asset to Debt Ratio and Net Worth to Debt Ratio); 3. KPRI SEJAHTERA Cooperative Financial Performance Based on Rentability Ratio in review of (Own Capital Rentability and Return On Assets (ROA)) 4. Level of Health Assessment KPRI SEJAHTERA Blitar District Agriculture Office 2014-2016. The results of this study provide the following conclusions: 1) Current ratio of 2014-2016 the average of 1,887.97%, the criteria is not good. 2) The quick ratio of 2014- 2016 the average is 1,887,97%, the criteria is not good. 3) Cash ratio of 2014 - 2016 the average is 47.41%, the criteria is not good. 4) Net worth to debt ratio in 2014 - 2016 average is 1,809,23%, good criteria. 5) The total asset to debt ratio of 2014 - 2016 the average is 1,909.23%, the criteria is good. 6) Rentability of own capital in 2014 - 2016 the average is 5.79%, the criteria is less good. 7) ROA of 2014-2016 the average is 5.65%, the criteria is less good. 8) Health Level Assessment KPRI SEJAHTERA year 2014 - 2016 otherwise Not Healthy.